A simplified point-of-service model for hepatitis C in people who inject drugs in South Africa - Elaine Saayman; Vanessa Hechter; Ndoliwe Kayuni; Mark W. Sonderup (BMC, 2023)
Abstract Background Globally, 9% of people who inject drugs (PWID), a key hepatitis C-infected population, reside in sub-Saharan Africa. In South Africa, hepatitis C seroprevalence in PWID is high. It is almost 84% in Pretoria and hepatitis C genotypes 1 and 3 predominate. Access to hepatitis C care for PWID is inadequate given low referral rates, socio-structural barriers, homelessness and limited access to harm reduction. Traditional care models do not address the needs of this population. We piloted a simplified complete point-of-service care model, a first of its kind in the country and sub-continental region. Methods Community-based recruitment from Pretoria's PWID population occurred over 11 months. Participants were screened with point-of-care rapid diagnostic tests for HBsAg (Alere Determine™), hepatitis C and HIV antibodies (OraQuick®). Qualitative HCV viremia was confirmed on site with Genedrive® (Sysmex), similarly at week 4, end of treatment and to confirm sustained virological response. Viremic hepatitis C participants were initiated on 12 weeks of daily sofosbuvir and daclatasvir. Harm reduction and adherence support, through directly observed therapy, peer support, a stipend and transport, was provided. Results A total of 163 participants were screened for hepatitis C antibody, and 66% were positive with 80 (87%) viremic. An additional 36 confirmed hepatitis C viremic participants were referred. Of those eligible to initiate treatment, 87 (93%) were commenced on sofosbuvir and daclatasvir, with 98% (n = 85) male, 35% (n = 30) HIV co-infected, 1% (n = 1) HBV co-infected and 5% (n = 4) HIV/HBV/HCV triple infected. Some 67% (n = 58) accessed harm reduction packs, 57% (n = 50) opioid substitution therapy and 18% (n = 16) stopped injecting. A per protocol sustained virological response of 90% (n = 51) was achieved with 14% (n = 7) confirmed reinfections following a sustained virological response. HCV RNA qualitative testing performance was acceptable with all sustained virological responses validated against a laboratory assay. Mild adverse effects were reported in 6% (n = 5). Thirty-eight percent (n = 33) of participants were lost to follow-up. Conclusion In our setting, a simplified point-of-service hepatitis C care model for PWID yielded an acceptable sustained virological response rate. Retention in care and follow-up remains both challenging and central to success. We have demonstrated the utility of a model of care for our country and region to utilize this more community acceptable and simplified practice.